Increase in cotton yield through improved leaf physiological functioning under the soil condition of reduced chemical fertilization compensated by the enhanced organic liquid fertilization - Shi, Xiaojuan; Hao, Xianzhe; Khan, Aziz; Li, Nannan; Li, Junhong; Shi, Feng; Tian, Yu; Nepal, Jaya; Wang, Jun; Luo, Honghai (Frontiers in Plant Science, 2023)
Low agricultural nutrient input efficiency remains a significant impediment for crop production globally. To address this issue in cotton agroecosystems, there is a need to develop sustainable crop nutrient management strategies to achieve high crop yields. We hypothesized that organic liquid fertilizer (OF) combined with reduced chemical fertilizer (CF) would enhance cotton yield by improving leaf functioning and soil properties. However, the underlying mechanism and its related process is poorly understood. This study explored the effects of OF combined with reduced CF on cotton yield, physiology and soil properties.Treatments included a single application of CF (CF: N, P 2 O 5 and K 2 O applied at 228, 131 and 95 kg ha −1 ) and combined applications of OF and CF (OF 0.6 −OF 1.4 ) in the following ratios: OF 0.6 , OF+60% CF; OF 0.8 , OF+80% CF; OF 1.0 , OF+100% CF; OF 1.2 , OF+120% CF; OF 1.4 , OF+140% CF. The result showed that compared with CF, OF 0.8 , OF 1.0 and OF 1.2 increased soil organic matter (SOM) content by 9.9%, 16.3% and 23.7%, respectively. Compared with CF, the OF 0.6 , OF 0.8 , OF 1.0 , and OF 1.2 treatments increased leaf area (LA) by 10.6−26.1%, chlorophyll content (Chl content) by 6.8−39.6%, and the efficiency of photosystem II (PSII) light energy (Y(II)), electron transfer rate of PSII (ETR) and photochemical quenching (qP) by 3.6−26.3%, 4.7−15.3% and 4.3−9.8%, respectively. The OF 0.8 treatment increased net photosynthetic rate (P n ), stomatal conductance (G s ) and transpiration rate (E) by 22.0%, 27.4% and 26.8%, respectively, resulting in higher seed cotton yield. The seed cotton yield and economic coefficient were positively correlated with P n , E, G s and Y(II) from the full boll stage to the boll opening stage. In summary, the OF 0.8 treatment can maintain a high SOM content and photosynthetic performance with reduced chemical fertilizer input without 3 sacrificing yield. The integration of OF+80% CF (OF 0.8 ) is a promising nutrient management strategy for highly efficient cotton production under mulch drip irrigation systems.